A categoria narrativa do personagem no fotojornalismo: A significação dos retratos a partir de sua estruturação morfemática - Casadei, Eliza Bachega [UNESP] (Universidade Estadual de Londrina, 2015)
In this article, we will discuss the processes involved in the construction of meaning in the narrative category character in photojournalistic images. We will discuss the notion that the character appears as an empty signifier that completes its meaning through morfematic-imagetic structuring and relational schemas between characters. From the study of the Hamon's work, we will analyze photographs from Frederik Buyckx, in their modes of character building.
Character in photojournalism: The meaning of pictures from its morphemic structure
Keywords: Character; Meaning construction; Narrative; Photojournalism